HUBUNGAN TINGKAT PENDIDIKAN IBU HAMIL DENGAN PENCAPAIAN KUNJUNGAN AWAL KEHAMILAN (K1)DI DESA PURWOJATI KECAMATAN NGOROKABUPATEN MOJOKERTO - Frilasari, Heni; Delta Surya Dewi, Tri (Jurnal Keperawatan Bina Sehat, 2014)
Antenatal care is an attempt to address maternal deaths that occur during pregnancy and childbirth. By doing prenatal care at least 4 times the one time in the first trimester, one in the second trimester, and twice in the third trimester. This study aims to analyze the relationship between level of education attainment visit pregnant women with early pregnancy (K1) in the Village District Purwojati Ngoro Mojokerto regency period from February to May 2012. In studies using crosssectional design with analytical studies. Samples taken 26r espondents. Sampling technique using a consecutive sampling and data collection taken from pregnant women and KMS observation sheet. Analysis of the data used is the Wilcoxon test statistic. From the survey results revealed the percentage of pregnant women who do not make a visit early in pregnancy (K1) 18 people (69.2%) where most have the basic education level (elementary, junior high). The results of Wilcoxon test statistics through SPSS for windows got the result Z=-4.519 and a value ρ= 0.000 <α (0.05). So H0 is rejected and H1 accepted to mean there is a relationship between level of education attainment visit pregnant women with early pregnancy (K1). Can be concluded that thel evel of education affects the motivation of pregnant women in early pregnancy visits (K1). In order to achieve the initial visit should be held counseling pregnant women for prenatal care as early as possible as late period regularly every month and once in posyandu, polindes and place-a place for medical care.Key words: educationlevel, pregnant women, K1.